State of the Art of the Technical Regulation for Precast Concrete Elements for Unifamiliar Housing - Villalobos Ramírez, Francisco (2025)
In Costa Rica, the prefabricated system of columns and horizontal tiles is one of the most used options in social housing projects developed by the BAHNVI. The BAHNVI is the mortgage housing bank of Costa Rica, it is in charge of assigning housing credits financed by the Government of Costa Rica to vulnerable sectors of the population in order to fulfill their housing needs. As a direct consequence, the supply of this product has increased considerably in recent years by small and medium-sized companies distributed throughout the national territory. As a way to ensure the good quality of these products the Technical Standards Institute of Costa Rica, INTECO, has developed a standard for prefabricated concrete elements for the construction of single-family housing using the system of columns and horizontal tiles. The first edition of this standard was published in 2013 and in February 2017 the second edition was published. This last edition exposes changes in normative aspects, experimental methods and sampling methods. Since the publication of the first edition of the standard, there has been a significant increase in the quality of the verification of this products and a great develop in research work on the subject. This paper describes the main national researches developed in the field and its relation with the evolution of technical regulations.